Stabilization of expansive soil using silica fume and lime - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan (Penerbit UMP, 2024)
Structures built on soft clays frequently encounter stability and settlement issues owing to the high compressibility, low shear strength, and poor permeability of such clay types. These characteristics often result in bearing capacity failure and excessive settlement, posing significant challenges to construction projects. Therefore, the study investigates the strength enhancement of expansive clay soil with the inclusion of various percentages and combinations of silica fume (SF) and lime (L). Hence, the mechanical characteristics of various mix ratios of SF and L are examined via the standard Proctor, and unconfined compressive strength (UCS). The samples were treated for 1, 7, 14 and 30 days and examined under the UCS tests. The experimental results show that the strength of the expansive clay significantly rises with the inclusion of SF and L at dissimilar mix ratios and curing days. The mixture of SF and L resulted in a significant strength increment of the kaolinite clay soil up to 80.22%.